Quality of Sexually Transmitted Infection Case Management Services in Gauteng Province, South Africa: An Evaluation of Health Providers' Knowledge, Attitudes, and Practices. Issue 1 (January 2016) - Ham, David Cal; Hariri, Susan; Kamb, Mary; Mark, Jennifer; Ilunga, Ricky; Forhan, Sara; Likibi, Mupatal; Lewis, David A.
Abstract : Background: The sexually transmitted infection (STI) clinical encounter is an opportunity to identify current and prevent new HIV and STI infections. We examined knowledge, attitudes, and practices regarding STIs and HIV among public and private providers in a large province in South Africa with a high disease burden. Methods: From November 2008 to March 2009, 611 doctors and nurses from 120 public and 52 private clinics serving patients with STIs in Gauteng Province completed an anonymous, self-administered survey. Responses were compared by clinic location, provider type, and level of training. Results: Most respondents were nurses (91%) and female (89%), were from public clinics (91%), and had received formal STI training (67%). Most (88%) correctly identified all of the common STI syndromes (i.e., genital ulcer syndrome, urethral discharge syndrome, and vaginal discharge syndrome). However, almost none correctly identified the most common etiologies for all 3 of these syndromes (0.8%), or the recommended first or alternative treatment regimens for all syndromes (0.8%). Very few (6%) providers correctly answered the 14 basic STI knowledge questions. Providers reporting formal STI training were more likely to identify correctly all 3 STI syndromes ( P = 0.034) as well as answer correctly all 14 general STI knowledge questions ( P = 0.016) compared with those not reporting STI training. In addition, several providers reported negative attitudes about patients with STI that may have affected their ability to practice optimal STI management. Conclusions: Sexually transmitted infection general knowledge was suboptimal, particularly among providers without STI training. Provider training and brief refresher courses on specific aspects of diagnosis and management may benefit HIV/STI clinical care and prevention in Gauteng Province. Abstract : Survey of knowledge, attitudes, and practices among sexually transmitted infection (STI) providers in Gauteng Province, South Africa, found that STI general knowledge and practices were suboptimal, particularly among providers with little STI training.